The Effectiveness of Peer Educators on the Level of Knowledge about Reproductive Health at Akelamo Community Health Center, Tidore - Suratni Abdurrahim; Rani Safitri (Universitas Muhamadiyah Manado, 2025)
Reproductive health is an important aspect in improving the quality of life of the community, but the level of knowledge about reproductive health is still relatively low due to cultural factors, social norms, and limitations of the educational methods used. This study aims to analyze the effectiveness of the peer educator method in increasing the level of reproductive health knowledge of the community in the Akelamo Community Health Center, Tidore. This study used a pre-experimental design with a one-group pretest-posttest approach. The study sample consisted of 24 respondents selected using a total sampling technique. The intervention was carried out through reproductive health education using the peer educator method in small groups. Measurements of knowledge levels were carried out before and after the intervention using a standardized questionnaire. Data analysis used the Wilcoxon test with a significance level of p < 0.05 . The results showed an increase in the average knowledge score from 56.3 before the intervention to 78.5 after the intervention. Statistical tests showed a significant difference between the levels of knowledge before and after the intervention (p = 0.001). These results indicate that the peer educator method is effective in increasing public reproductive health knowledge .